PERANCANGAN DAN PEMBUATAN ALUR PENDAFTARAN PASIEN RAWAT INAP DARI IGD MENGGUNAKAN MEDIA AKRILIK TENT HOLDER DI RSUD KABUPATEN JOMBANG - Miftakhul Jannah; Dea Allan Karunia Sakti; Ahmad Fauzi (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
Based on the results of observations, it is known that in the emergency room admission room there is no flow for registering inpatients, which causes the patient's family to be confused about the requirements and steps taken in registering an inpatient. The method used in this research is a qualitative method with a case study approach. The instruments used are interviews and observations. The results of the research show that the priority problem is problems related to the patient registration system, which is less than optimal. The results of the root cause analysis show that there are four factors causing the problem (man, method, machine, and environment). The design of the inpatient registration flow from the ER was made based on the results of interviews and observations and was based on the applicable SOP. The results of observing the implementation for two days revealed that there were 17 people in charge of patients who had observed the flow of inpatient registration from the ER. There needs to be socialization regarding the flow of registration of inpatients from the emergency room as well as monitoring and evaluation of the flow every three months.